Teachers’ emotional appraisals and the reframing of student change in post-pandemic schools - Gaines, Rachel E.; Chang, Mei-Lin; Palmer, Melinda; Mosley, Kristen C. (Frontiers in Education, 2025)
IntroductionThe return to “normal” schooling after the COVID-19 pandemic reactivated many of the emotional, instructional, and moral tensions teachers experienced during emergency remote teaching. Yet, little is known about how teachers’ emotional appraisals of post-pandemic classrooms intersect with deficit-oriented “learning loss” discourses. Guided by appraisal theory and Frenzel’s reciprocal model of teacher emotions, this qualitative study examined how mid- and late-career teachers interpreted perceived changes in students and how these appraisals shaped their emotions, emotion regulation, and adoption of or resistance to deficit framings.MethodsTen K–12 teachers from the southeastern United States participated in semi-structured interviews. Data were analyzed through an inductive, consensual qualitative approach and a modified phenomenographic design.ResultsFindings revealed that teachers most frequently appraised post-pandemic “changes in students” as gaps in (a) content knowledge, (b) self-regulation, and (c) social-emotional development. These appraisals were typically experienced as goal-incongruent and elicited unpleasant emotions—especially frustration, inefficacy, and stress. However, teachers who engaged in cognitive reappraisal and empathic perspective-taking maintained more pleasant emotions and resisted deficit narratives, instead interpreting students’ behaviors as adaptive responses to disruption.DiscussionThe study highlights how teachers’ emotional appraisals function as a mechanism linking policy discourse, classroom experience, and teacher wellbeing. Findings suggest the need for professional learning that explicitly supports teachers’ emotion regulation and critical reflection on deficit narratives, alongside policy reforms that temper accountability pressures in post-crisis schooling. Theoretical contributions include linking emotion regulation strategies to the adoption or rejection of deficit perspectives and demonstrating how emotional responses vary within appraisal theory based on the type of goal that is threated.